EFEKTIFITAS BLADDER TRAINING TERHADAP PERCEPATAN PENGELUARAN URINE PADA IBU POSTPARTUM PERVAGINAM - Risdiana Melinda Naibaho (Jurnal Keperawatan Priority, 2022)
Complications after childbirth can occur if there is no continuous treatment that can end in death, including urinary retention, the bladder is pushed up and down, thus preventing the uterus from contracting properly. Bladder emptying with leader training to restore normal urinary patterns by stimulating urine output to allow spontaneous bladder emptying. This study aims to identify the effectiveness of bladder training on the prevention of urinary retention in postpartum mothers. This research method is a case study using a quasi-experimental research design with a non-equivalent control group approach. The sample were 32 respondents. Data collection using incidental sampling technique was in accordance with the inclusion criteria for normal postpartum mothers in the VK room of the Sidikalang General Hospital using a questionnaire instrument with an observation sheet. The data analyzed by using the different paired t test. The results showed that in the intervention group, the results of the paired t test were t-test values ​​= 2.147 tables 1.753 (t-count> t-table), while in the control group the results of the paired t-test were different, 1.275 <1.753 (t count < t table) meaning Bladder training is effective in accelerating urine output. Bladder training can be considered as a non-fatmacological therapy to prevent urinary retention. It is recommended to health workers to be able to apply it as an independent action material to prevent urinary retention in postpartum mothers.